TEACHING METHOD AND ITS IMPACT ON ENGLISH ACADEMIC PERFORMANCE THROUGH LEARNING INTEREST AS A MODERATOR VARIABLE AMONG THE STUDENTS OF MTSN 2 KOTA KEDIRI - Erwin Hari Kurniawan (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
This research aims at analyzing a significant effect of the following variables: 1) Teaching method on English academic performance; 2) Learning interest on English academic performance; 3) Teaching method on learning interest; and 4) Teaching method on English academic performance through learning interest as a moderator variable. To prove those questions, this research adopts quantitative approach with survey method. The samples are 207 students who are taken through simple random sampling calculated using Slovin formula. The data is analyzed through path analysis. It is used regression test including simple and multiple linear regressions. The result of this research indicates: 1) Teaching method has a significant effect on English academic; 2) Learning interest has a significant effect on English academic performance; 3) Teaching method has a significant effect on learning interest; and 4) Teaching method has an indirect impact on English academic performance through learning interest as a moderator variable about 18,3%. Meanwhile the direct effect is 3,4%. The result shows that the indirect effect is greater than direct effect in which the effect of teaching method on English academic performance is considered as the direct effect and the effect of teaching method on English academic performance through learning interest as a moderator variable is considered as the indirect impact. It is recommended to the teachers to evaluate their teaching abilities that foster students’ learning interest then academic performance automatically increases.